Artificial Intelligence in the Indian Legal System: Balancing Benefits and Risks - Dahiya, Nidhi; Venu, Shristi (International Journal of Law, Human Rights and Constitutional Studies; Vol 7 No 1 (2025): International Journal of Law, Human Rights and Constitutional Studies, 2025)
One of the most recent discussions in the wide framework of the Indian legal system is whether or not to incorporate significantly advanced artificial intelligence into the delivery of justice. As the truth emerges that the growth and relevance of AI are unavoidable, the only question before the court is, “Will this technology be beneficial or detrimental to its use?” This study seeks to go more into the disparity of views and perspectives on the benefits and drawbacks of these instruments. It examines the current situation, taking into account the practical con sequences as well as the verbal analogy offered in this respect, and their applicability in terms of improving justice delivery. The purpose of this paper is to highlight the accessibility of such tools to laymen and how they could revolutionize the system not only for professionals but also for those seeking justice. Individuals without legal competence can better navigate the system and advocate for their rights if they have access to simple platforms and tools. This shift towards accessibility has the potential to level the playing field and empower marginalized communities in their pursuit of justice.